"Life-altering": A qualitative analysis of social media birth stories from mothers of children with Down syndrome. (December 2022) - Kammes, Rebecca R; Lachmar, E Megan; Douglas, Sarah N; Schultheiss, Hannah
Perinatal depression/anxiety is a significant concern for mothers of children with Down syndrome. This is influenced by the way the Down syndrome diagnosis is shared with parents. This study examined social media posts from mothers regarding experiences of the birth of their child with Down syndrome. Forty-three total stories were coded using thematic content analysis. Results highlighted the experiences of mother's who received a diagnosis of Down syndrome for their newborn. Two themes were found with relevant subthemes (i.e., receiving the diagnosis—mother's intuition, confirmation of the diagnosis, influence of potential health concerns, initial emotions, impact of the medical professional; Processing the diagnosis—life-altering, child not meeting expectations, reframing the diagnosis, impact of partner and others). Findings highlight the need for medical personnel to understand this identity-changing process, as perinatal depression/anxiety looks different for these mothers. There is also a need to help them engage in services accordingly.